EVALUASI PROGRAM PRAKTIK INDUSTRI LUAR NEGERI DI FAKULTAS TEKNIK UNIVERSITAS NEGERI YOGYAKARTA - Yulian Ageng Prasetyo; Bambang Sulistyo (Universitas Negeri Yogyakarta, 2020)
The purpose of this research to determine the achievement of the implementation of oversais industry practices in the Faculty of Engineering, Yogyakarta State University in 2018 in terms of Context, Input, Process, and Product evaluation. This research was included in a descriptive research using a quantitative approach. Data collection was taken through questionnaires and interviews. Data analysis used descriptive statistics and presented in the form of tables and histograms supported by interview data. The results showed that. (1) Achievement of context evaluation included in the excellent category of 87,5% with 28 respondents and an average total score of 12,5. (2) Achievement of input evaluation included in the excellent category of 90,63% with 29 respondents and an average total score of 80,7. (3) Achievement of process evaluation included in the excellent category of 75% with 24 respondents and an average total score of 131,5. (4) Achievement of product evaluation included in the excellent category of 81,25% with 26 respondents and an average total score of 16,8.